Grape berries biochemical shifts from vines under summer stress treated with kaolin and silicon mixtures - Pereira, Sandra; Baltazar, Miguel; Branco, Zélia; Monteiro, Ana; Serrano, A. Sérgio; Morales, Adela Mena; Cruz, Rebeca; Casal, Susana; Balfagón, Damián; Moura, Renata; Moutinho-Pereira, José; Dinis, Lia-Tânia (Frontiers in Plant Science, 2025)
IntroductionClimate change is intensifying abiotic stress in viticulture, with higher temperatures, water deficits, and increased solar radiation directly affecting grape berry development, biochemical balance, and overall fruit quality. These challenges compromise the delicate balance of sugars, acids, phenolic compounds, and aromatic profiles that define the sensory attributes and typicity of the resulting wine. Innovative practices are therefore needed to sustain fruit quality and composition under increasingly variable and extreme climatic conditions. Silicon (Si) and kaolin (Kl) have already shown highly positive effects in mitigating the impacts of climate change on grapevines.MethodsBuilding on this, the aim of this study was to test their combined foliar application to simultaneously alleviate drought and heat stress and enhance berry quality. An integrated assessment was conducted over two growing seasons in a commercial vineyard (Vitis vinifera L. cv. Touriga Franca) located at Quinta de Ventozelo (Douro Demarcated Region, Portugal) to evaluate the effects of combined Kl (2%) and Si foliar sprays at different concentrations (2–8%). The study included analyses of fruit biochemical composition, must quality, cuticular wax profile, histological traits, carbon isotope discrimination (d13C), hormonal balance, and yield parameters.Results and discussionResults showed that Si and Kl treatments modulated secondary metabolite accumulation (phenols, flavonoids, anthocyanins, and tannins) in a season- and stage-dependent manner, with significant increases under milder environmental conditions, particularly in seasons with lower heat and drought stress. This suggests that these products can act as elicitors or stress mitigators, depending on the environmental context. Treated vines maintained higher organic acid levels and lower probable alcohol content, indicating an improved sugar–acid balance. Moreover, the treatments influenced the cuticular wax composition, enhancing triterpenoid content and increasing cuticle thickness and epidermal cell size, which, together with enriched d13C values, support improved water-use efficiency. The hormonal profiles confirmed the role of Si and Kl in fine-tuning stress and growth signals, contributing to better fruit robustness.ConclusionsThese findings demonstrate that the combined foliar application of kaolin and silicon is a promising tool to protect grape berry quality by modulating biochemical composition, cuticular wax profile, histological traits, isotopic signature, and hormonal balance, helping maintain fruit integrity and quality, and compositional stability under the ongoing challenges of climate change.